DETERMINAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN LOMBOK BARAT - RUSLI AMRUL; NI NYOMAN YULIATI; I NENGAH ARSANA; ASYSYIFA SAFIA SAWALISARI (GANEC SWARA, 2024)
This study aimed to analyze factors that influence the quality of local government    financial statements (empirical study in OPD’s Lombok Barat regency). The Population of this study is in the scope of the OPD’s Lombok Barat regency that is involved in the financial administration of local. Samples were taken using purposive sampling. The criteria are based on the employess involved in the preparation of financial statements. Each of OPD is taken 5 (five) respondents involved in the preparation of financial satatements consisting of the head and treasurers of sub-section of finance service Lombok Barat regency, staff information system of sub-section of finance agancy and other staff who know related finance in agency Lombok Barat regency. Data obtained by distributing questionnaires to 81 respondents in 21 agency Lombok Barat regency. Based on the result of questionnaire processing using multiple linear regression analyze, t test known partially variable of human resource competence, the application of government accounting standards and, the utilization information technology affect quality of local government financial reporting Lombok Barat regency. Instiead of internal control system has no significant effect on the quality of the financial statements of the Lombok Barat regency